Radio formāta specifika: satura un auditorijas aspekti. „Baltkom radio” analīze - Šindikova, Natālija (Latvijas Universitāte, 2011)
Bakalaura darba „Radio formāta specifika: satura un auditorijas aspekti. „Baltkom 93,9 FM radio” analīze” ietvaros tiek analizēta minēta radiostacijas darbība tās raidījuma saturs un struktūra. Komunikācijas problēma tiks pētīta no diviem aspektiem: formāta problemātikas puses un no klausītāju vēlmēm un cerībām attiecībā uz konkrēto radiostaciju. Darbā tiek izmantotas dažādas pētīšanas metodes. Kā kvalitatīvās pētījuma metodes tika izmantotas kontentanalīze. Lai noskaidrotu auditorijas viedokli par atsevišķiem radiostacijas raidījumiem un formātu kopumā, pētījuma ietvaros tiks veikts fokusa grupu pētījums. Savukārt lai izprastu radio Baltkom 93,9 FM formāta News/Talk saturu un specifiku tiek uztaisīta raidījuma satura analīze. Kā arī pētnieciskajā daļā pievērsīšos Baltkom Radio diskusijas raidījuma kontentanalīzei. Atslēgvārdi: radio, radiofonija, radiostacijas, formāts, žanrs, komerciālais radio, sabiedriskais radio, New/Talk uttl.

The goal of work is answer the question – how well in content and commercial aspects commercial radio with analytical format could work in Latvian market. In this work will analyze the format transformation, focusing on the audience’s wishes and the specifics. In work will be used theoretical materials on the radio format creation, radio journalistic, news production and moderation. Will be analyzed "Baltkom radio 93.9 FM" as a phenomenon, because it is the only commercial radio station in Riga, which operates 12 hours a day News/Talk format in two languages. News and news reports are at least 70-80% of this radio broadcasting. Another feature is the fact, that "Baltkom radio 93.9 FM" ensure in Russia recorded radio station "Echo Moskvy" (Эхо Москвы) retransmission here in Latvia. "Baltkom radio 93.9 FM" music format can be defined as Smooth/Jazz, which is quite a rare genre in Latvian music radio station broadcast. To find the audience views on certain radio broadcasts and format as a whole, the study will be carried out focus group method analyze. By contrast, in-depth interviews will be used conversation with "Baltkom radio 93.9 FM” program managers and news service managers to understand the format making principles and problems, as well as on what criteria are selected news, music and selected for broadcast design. The empirical part of this work is focused on "Baltkom radio 93.9 FM” agenda, for analytical method selecting the content analysis and data analysis TNS database to study the social portrait of the audience. This work will help to understand which quality conditions are necessary for commercial success and existence of radio station with an analytical, informative format that is not based on the music formats. Keywords: radio, broadcasting, broadcast, News/Talk format, programming, commercial and public radio station
Radio format specificity: the content and audience aspects. Radio "Baltkom" analysis
Keywords: Komunikācijas zinātne